Modality and task complexity effects on second language production in CMC - Adams, Rebecca; Nik Aloesnita, Nik Mohd Alwi; Umi Kalsom, Masrom (National Foreign Language Resource Center, 2023)
Two decades of research on computer-mediated communication (CMC) in language learning settings has shown that integrating technology and communication leads to distinct benefits for language learning, including positive impacts on motivation, anxiety, and engagement in second language communication (Sauro, 2011). However, the majority of this research has been conducted among learners communicating via text while real-world language users are increasingly likely to communicate online in audio and video modes (Peterson, 2010). Audio and video CMC has been shown to lead to more participation (RossellÁguilar, 2013), different uses of communication strategies (Hung & Higgins, 2016), more focus on form (Bueno-Alastuey, 2010), and higher motivation (Gleason & Suvorov, 2012; Wehner et al., 2011) among second language (L2) learners. Little is known, however, about learner language production in different CMC modalities, which influences how CMC can be integrated into teaching. The current study focuses on L2 learners’ production during communicative tasks in text and video CMC. Two versions of the task were created by manipulating the task complexity variable task structure (Robinson, 2011). Production data were analyzed using measures of syntactic and lexical complexity, linguistic accuracy, and quantity of language produced. The results suggest that complexity and modality both impact the lexical complexity of language production, and that modality also affects the quantity of language produced.